Digital tool for mapping suitable areas for Alternate Wetting and Drying (AWD) adoption for Vietnam - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The AWD suitability mapping methodology has been validated in a stakeholder consultation work shop in An GIang province, Vietnam. The digital tool was developed using local data and introduced to various groups of policy makers and practitioners who work in mitigation in rice. It is available for download and use.